Commentary on “Constructing New Theory for Identifying Students with Emotional Disturbance” - Cheri Ann Hernandez (Grounded Theory Review: An International Journal, 2012)
First we would like to com m end and thank Dr. Dori Barnett for her willingness to subm it her work for the purpose of acting as a constructivist grounded theory research exem plar, with the understanding that she was subjecting her work to the scrutiny of researchers from another grounded theory tradition. We have developed this com m entary on Dr. Barnett’s work in the spirit of respect and colleagueship that was recom m ended in the guest editorial of this Grounded Theory Review issue. We acknowledge that her study is very significant and will be very useful to practitioners. Our purpose is to use the research exem plar to identify differences between this type of research and that of classic grounded theory. Readers who have been schooled and grounded in classic grounded theory methodology will have noticed at least five m ajor differences between the constructivist grounded theory exemplar and classic grounded theory. This com m entary will delineate and describe these differences.